Genre-based approaches and ESL/EFL writing: a review of the literature - Liu, Hongjian; Ismail, Lilliati; Ahmad, Norhakimah Khaiessa (Sciedu Press, 2023)
This article presents a comprehensive systematic literature review of the associations between genre-based approaches (GBAs) and English as a second language (ESL) or English as a foreign language (EFL) writing. It provides an overview of GBAs and second language (L2) writing. The review further elaborates on the theoretical backgrounds of GBAs and ESL/EFL writing. The article then critically reviews 38 studies conducted on GBAs and ESL/EFL writing in the past 20 years (2003-2023). A methodological review was also performed to analyze the various research methods employed by previous researchers. Four major themes of research on GBAs and ESL/EFL writing were identified: research articles’ writing, thesis or dissertations writing, argumentative writing, and other types of professional writing. Additionally, three major methodological approaches were identified: qualitative, quantitative, and mixed methods. The article culminates by discussing the implications of the results of this review and recommends promising directions for future research.